Central retinal artery occlusion with cilioretinal sparing in a patient with Eisenmenger syndrome. Issue 2 (28th February 2022) - Gupta, Abhishek; Singh, Prabhakar; Sanepalli, Sravani Reddy; Raj, Amit
Abstract : A young boy in his 20s presented with sudden diminution of vision in right eye 2 days ago. Best-corrected visual acuity was hand movement in right eye and 20/20 in left eye. Funduscopy demonstrated diffuse retinal opacification and swelling at the posterior pole with a cherry red spot at the macula. There was sparing of the superonasal macula with a patent cilioretinal artery. OCT showed diffuse inner retinal thickening of the temporal macula. He was diagnosed as central retinal artery occlusion with cilioretinal sparing in right eye. He was a known case of Eisenmenger syndrome secondary to a large congenital ventricular septal defect. Medical history was notable for prominent pulmonary hypertension and shortness of breath on exertion. Physical examination revealed a harsh systolic murmur. Extremities showed digital erythema and severe clubbing. Chest X-ray demonstrated cardiomegaly. Laboratory examination revealed haemoglobin—220 g/L, haematocrit—60%, serum iron—20 µg/dL.